Microbial Diversity and Activity During the Biodegradation in Seawater of Various Substitutes to Conventional Plastic Cotton Swab Sticks - Jacquin, Justine; Callac, Nolwenn; Cheng, Jingguang; Giraud, Carolane; Gorand, Yonko; Denoual, Clement; Pujo-Pay, Mireille; Conan, Pascal; Meistertzheim, Anne-Leila; Barbe, Valerie; Bruzaud, Stéphane; Ghiglione, Jean-François (Frontiers in Microbiology, 2021)
The European Parliament recently approved a new law banning single-use plastic items for 2021 such as plastic plates, cutlery, straws, cotton swabs and balloon sticks. Transition to a bioeconomy involves the substitution of these banned products with biodegradable materials. Several materials such as PLA, PBAT, PBS, PHBV, Bioplast and Mater-Bi could be good candidates to substitute cotton swabs, but their biodegradability needs to be tested under marine conditions. In this study, we described the microbial life growing on these materials and we evaluated their biodegradability in seawater, compared to controls made of non-biodegradable PP or biodegradable cellulose. During the first 40 days in seawater, we detected clear changes in bacterial diversity (Illumina sequencing of 16S rRNA gene) and heterotrophic activity (incorporation of 3H-Leucine) that coincided to the classic succession of initial colonization, growth and maturation phases of a biofilm. Biodegradability of the cotton swab sticks was then tested during another 94 days under strict diet conditions with the different plastics as sole carbon source. The drastic decrease of bacterial activity on PP, PLA and PBS suggested no bacterial attack of these materials, whereas bacterial activity in PBAT, Bioplast, Mater-Bi and PHBV presented similar response to the cellulose positive control. Interestingly, the different bacterial diversity trends observed for biodegradable versus non-biodegradable plastics allowed to describe potential new candidates involved in the degradation of these materials under marine conditions. This better understanding of the bacterial diversity and activity dynamics during the colonization and biodegradation processes contributes to an expanding baseline to understand plastic biodegradation in marine conditions and provide a foundation for further decisions on the replacement of the banned single-used plastics.